2019
DOI: 10.14744/bej.2019.52724
|View full text |Cite
|
Sign up to set email alerts
|

Objective Accommodation Measurements by Using a New Autorefractometer Device

Abstract: To measure the value of objective accommodation amplitude (AA) in patients using the new autorefractometer device and to evaluate the effects of age, refraction errors, pupil diameter on objective AA measurements. Methods: Three hundred subjects who were divided into five groups according to age were enrolled in this study. AA and pupil diameter were measured three times from both eyes using Tonoref III (NIDEK Co., Ltd.). Results: The mean AA was 1.6325±0.061 Diopter (D) (0.13-9.11 D). The mean AA values were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
1
0
0
Order By: Relevance
“…In addition, the pupil diameter decreases with age. In the study by Ozulken et al (19), it was reported that the pupil diameter decreased with age, as in our study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, the pupil diameter decreases with age. In the study by Ozulken et al (19), it was reported that the pupil diameter decreased with age, as in our study.…”
Section: Discussionsupporting
confidence: 84%